Optimalisasi Potensi Usaha Mikro dan Kecil Melalui Penerapan Strategi Pengembangan Bisnis Berkelanjutan - Hery Fadly (Yayasan Habiburrahman Jamalu Bina Ummat, 2024)
micro and small businesses (MSBs) through the implementation of sustainable business development strategies. A partnership approach is employed with MSBs to implement sustainable business practices, including environmental, social, and economic management. The development method involves training, consultation, and the implementation of sustainable practices. The research findings indicate improved performance of MSBs and their positive impact on the environment and local communities. In conclusion, the application of sustainable business development strategies can enhance the sustainability of MSBs and their contribution to community development.